Genesis, with an introduction to narrative literature - Coats, George W. (Grand Rapids, Mich. : W.B. Eerdmans Pub. Co., 1983)
In the introduction to this volume, George Coats discusses narrative in general and the principal Old Testament narratives in particular. He then sets the book of Genesis in its larger Old Testament context, analyzing its major sections and subsections. Each of the succeeding chapters treats one of the major sections. A bibliography heads each chapter, and a shorter bibliography of relevant works appears at the end of each unit. The book concludes with genre and formula files, which list all the relevant genres and formulas and the texts in which they occur.
The Pentateuch / Hexateuch : the framework -- The patriarchal theme (The Book of Genesis) : the framework -- The primeval saga -- The individual units -- The Abraham saga -- The individual units -- The Isaac saga -- The individual units -- The Jacob saga -- The individual units.
Includes bibliographical references.
Keywords: Bible. -- Criticism, interpretation, etc; Narration in the Bible; Criticism, interpretation, etc